Synthesis on the Impact of Land Cover Conversion towards Water Quantity and Quality - Sudjatmiko, Henny; Bisri, Muhammad; Limantara, Lily Montarcih; Roebijoso, Jack (Journal of Ecohumanism, 2025)
This research intends to establish a policy on watershed management based on the land use recommendation and an analysis of land cover conversion to per-urban location towards water quality and discharge which many sub-watersheds in Indonesia are in critical condition due to the frequent event of flooding, drought, and landslide. It is further worsened by the changes of land cover in the watershed that causes to increase in surface runoff which also affects the water quality in the watershed. Watershed condition can be restored by management if the correct implementation and regulation is effective. Out of 458 watersheds in Indonesia, 60 of them were very critical, 222 were critical, and the remaining 176 were in endangered condition. One of the critical watersheds is Ciliwung watershed. Furthermore, public participation is a key in managing watershed. The methodology consists of collecting the primary data as a benchmark for simulation by using SWAT; the regression model is used for covering the water quality while the water discharge analysis is performed through hydrological simulation. Then socio-economic survey is conducted to evaluate public willingness and capacity to participate in the watershed management. The result of simulation shows that sediment and nitrate is positively affected by water discharge while phosphate is negatively affected by it. The conversion of forest into agriculture significantly increases the nitrate and sediment production in while phosphate is not really affected. Meanwhile, in the watershed overall, surface runoff, nitrate, and phosphate are increasing drastically. The result of survey shows that most people that are living in the watershed do not have the funding or yard to participate in the watershed management. This result is a recommendation which reduces the agriculture land use by 10% and allocating it for water management.